The spatial conditioning in the incidence of depressive and neurotic disorders in a medium-size Polish town - Gorczyca, Piotr Wacław; Ścisło, Piotr; Wesecka, Agnieszka; Kozak, Marcin; Sobiś, Jarosław (Current Problems of Psychiatry, 2013)
Background: Most of research studies conducted so far have shown a frequent incidence of depression and neuroses in cities compared to rural and to suburban areas. Aims: We wanted to compare the geographic distribution of affective and neurotic disorders in Polish medium-size town. Methods: The following research work was carried out in a medium-size town based on address data of people placed in psychiatric hospitals for affective and neurotic disorders in the years 1989-2002. In order to study the differences among particular districts of the town the test for two proportions was applied. Results and Conclusions: The analyzed group of persons included 311 patients, 141 men and 170 women. It was indicated that patients more frequently lived in the centers of towns as well as women aged 20-29 year in postindustrial districts and women (40-49) and men (50-59) in districts with city housing projects. It should be mentioned that more patients lived in the center of towns, but also in postindustrial districts and in districts with city housing projects.